2022
DOI: 10.1007/s00203-022-02757-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial adaptation to different environmental conditions: molecular perspective of evolved genetic and cellular systems

Abstract: Microorganisms are ubiquitous on Earth and can inhabit almost every environment. In a complex heterogeneous environment or in face of ecological disturbance, the microbes adjust to fluctuating environmental conditions through a cascade of cellular and molecular systems. Their habitats differ from cold microcosms of Antarctica to the geothermal volcanic areas, terrestrial to marine, highly alkaline zones to the extremely acidic areas, and freshwater to brackish water sources. The diverse ecological microbial ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(32 citation statements)
references
References 185 publications
0
30
0
2
Order By: Relevance
“…The taxonomic profiling and functional gene annotation of microbial communities of river Ganga (sediment) using whole-genome MGs have also been done (Rout et al 2022 ). Several other research groups have identified novel bacteria from different sites including extreme environments like hot springs, deserts, and deep-sea sediments for bioprospecting using a MG approach (Tang et al 2018 ; Najar et al 2020 ; Alotaibi et al 2020 ; Zhu et al 2022 ; Wani et al 2022b ). Global ocean sampling revealed about 40 million non-redundant novel genes from more than 30,000 species, whereas over 97% of the 150 million genes reported in topsoil globally cannot be found in the existing gene catalogue.…”
Section: Metagenomics (Mgs): Gateway To Microbial and Enzyme Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomic profiling and functional gene annotation of microbial communities of river Ganga (sediment) using whole-genome MGs have also been done (Rout et al 2022 ). Several other research groups have identified novel bacteria from different sites including extreme environments like hot springs, deserts, and deep-sea sediments for bioprospecting using a MG approach (Tang et al 2018 ; Najar et al 2020 ; Alotaibi et al 2020 ; Zhu et al 2022 ; Wani et al 2022b ). Global ocean sampling revealed about 40 million non-redundant novel genes from more than 30,000 species, whereas over 97% of the 150 million genes reported in topsoil globally cannot be found in the existing gene catalogue.…”
Section: Metagenomics (Mgs): Gateway To Microbial and Enzyme Miningmentioning
confidence: 99%
“…Metagenomics offers a gateway to overcome this problem (Handelsman 2004 ; Wani et al 2022a ). MGs in association with other meta-omics approaches are proving to be the standout approach for the identification of novel uncultivable microorganisms capable of MP-remediation (Bharagava et al 2018 ; Wani et al 2022b ). This review offers a comprehensive outlook of the MP threat around the globe besides highlighting the fundamental MP remediation studies mediated by microorganisms isolated through culture-dependent and culture-independent approaches.…”
Section: Introductionmentioning
confidence: 99%
“…These systems are not only normal, but are necessary for survival. It is known that proteins are the main components of an organism’s structural, enzymatic, hormonal, protective, transport, and homeostatic functions, among others [ 1 ]. Proteins must obtain three-dimensional structures to perform their biological functions; however, environmental stress factors promote protein unfolding [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hot springs, as representatives of extreme environments, have been shown to have highly diversified and abundant microbial communities, which still exist many yet uncultured and unexamined microorganisms [ 1 , 2 ]. These microorganisms may have evolved various metabolic systems to adapt to the local specific environment [ 3 , 4 ], such as genes related to carbohydrate degradation of Candidatus Bathyarchaeia for thermal adaptation to terrestrial geothermal habitats [ 5 ] and genes related to light sensing and absorption of Cyanobacteria to cope with fluctuating environments [ 6 ]. A wide range of abiotic environmental factors has been proven to shape the hot spring microbial community structures and diversity, with pH and temperature considered the most critical factors [ 7 – 10 ].…”
Section: Introductionmentioning
confidence: 99%